The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1289/ehp.01109711
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to environmental tobacco smoke and heart rate variability.

Abstract: Environmental tobacco smoke (ETS) has been associated with cardiovascular mortality. Pathophysiologic pathways leading from ETS exposure to cardiopulmonary disease are still being explored. Reduced cardiac autonomic function, as measured by heart rate variability (HRV), has been associated with cardiac vulnerability and may represent an important pathophysiologic mechanism linking ETS and risk of cardiac mortality. In this study we evaluated acute ETS exposure in a commercial airport with changes in HRV in 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 35 publications
9
85
1
3
Order By: Relevance
“…Previous studies have reported HRV associations with ambient PM air pollution exposure (Gold et al 2000;Liao et al 1999;, occupational PM exposure (Magari et al 2001), and PM exposure from secondhand cigarette smoking in an airport smoking lounge (Pope et al 2001). A previous study that used 24-hr ambulatory ECG monitoring was also conducted along the Wasatch Front in Utah , but it had only seven participants with a total of 39 observations and had air pollution monitoring only for PM ≤ 10 µm in aerodynamic diameter (PM 10 ).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported HRV associations with ambient PM air pollution exposure (Gold et al 2000;Liao et al 1999;, occupational PM exposure (Magari et al 2001), and PM exposure from secondhand cigarette smoking in an airport smoking lounge (Pope et al 2001). A previous study that used 24-hr ambulatory ECG monitoring was also conducted along the Wasatch Front in Utah , but it had only seven participants with a total of 39 observations and had air pollution monitoring only for PM ≤ 10 µm in aerodynamic diameter (PM 10 ).…”
Section: Discussionmentioning
confidence: 94%
“…4,28 Our observations are in agreement with the findings of Pope, who described a short-term decrease in all HRV domains after acute exposure to ETS, but with relatively high standard errors in HF. 12 LF, which is considered to represent both sympathetic and parasympathetic activities, 29 was lower in subjects with higher ETS exposure. We also observed ETS-associated increases in heart rate and, more weakly, in DBP, consistent with increases in sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 94%
“…Short-term effects have been described by Pope, who found a reduction in HRV in 16 never smoking subjects equipped with Holter monitors, who were moved from the non-smoking section of an airport to the smoking lounge. 12 Reports from the 1991 SAPALDIA (Swiss Cohort Study on Air Pollution and Lung Diseases in Adults) study 13 describe the effects of ETS on respiratory symptoms in never smokers 14 and on lung function in asthmatics. 15 In the follow-up study (SAPALDIA 2), we also show a higher probability of the development of asthma in subjects exposed to ETS.…”
Section: Introductionmentioning
confidence: 99%
“…HRV measurement was performed between 0600 and 1300 at room temperature between 201C and 301C using a twochannel (five-lead) electrocardiogram (ECG) monitor (Trillium 3000; Forest Medical, East Syracuse, NY, USA) according to published protocol (Pope et al, 2001). The ECG was recorded for approximately 7 min with the subject seated after a 5-min rest (sampling rate of 256 Hz per channel).…”
Section: Hrv Measurementmentioning
confidence: 99%